Job Creation or Destruction? Labor Market Effects of Wal-Mart Expansion - Basker, Emek (The Review of Economics and Statistics, 2005)
This paper estimates the effect of Wal-Mart expansion on retail employment at the county level. Using an instrumental variables approach to correct for both measurement error in entry dates and endogeneity of the timing of entry, I find that Wal-Mart entry increases retail employment by 100 jobs in the year of entry. Half of this gain disappears over the next five years as other retail establishments exit and contract, leaving a long-run statistically significant net gain of 50 jobs. Wholesale employment declines by approximately 20 jobs due to Wal-Mart's vertical integration. No spillover effect is detected in retail sectors in which Wal-Mart does not compete directly, suggesting Wal-Mart does not create agglomeration economies in retail trade at the county level.